Do Renewable Energy and the Real Estate Market Promote Environmental Quality in South Africa: Evidence from the Bootstrap ARDL Approach - Jahanger, Atif; Balsalobre-Lorente, Daniel; Samour, Ahmed; Joof, Foday; Ali, Mumtaz; Tursoy, Turgut (Mdpi, 2022)
Recent empirical research indicates that South Africa's present level of wealth and energy, given its fast-expanding population, is unsustainable. Studies in this domain focus on the impact of economic growth and energy use on environmental quality; the role of the real estate market on environmental quality in South Africa is ignored in the emerging literature. The current study aims to deliver a fresh empirical analysis in this context by analyzing the impact of South Africa's real estate sector expansion and renewable energy sources on carbon emissions. Using the newly developed bootstrap autoregressive distributed lag (ARDL) approach, the results of the empirical investigation showed that renewable energy improves South Africa's environmental quality. The current research also shows that the South African real estate industry has a negative impact on the environment. According to the current research, South African policymakers should create new regulations for the sustainable real estate sector to improve environmental quality by encouraging the usage of and investment in renewable energy.
Keywords: ARDL; South Africa; real estate market; energy; income